Effects of Innovation and Economic Freedom on Female Economic Inclusion - Pamela E. Ofori; Isaac K. Ofori; Paolo Castelnovo (ZBW - Leibniz Information Centre for Economics, 2024)
The Sustainable Development Goal 5 emphasises the need to achieve gender parity in economic participation. Perusing the extant scholarship on female economic inclusion in Africa, we identify two pressing gaps. First, we find that previous studies have not explored how innovation affects female economic inclusion (FEI). Second, we note that prior studies have not examined the interactive effect of innovation and economic freedom on FEI. This study addresses these gaps by using macro data from 1995-2022 for a sample of 51 African countries. Findings from the two-step system GMM estimator reveal the following: (1) innovation reduces FEI, whereas economic freedom increases it, and (2) economic freedom moderates innovation to promote FEI. Further, we find that this positive total effect of innovation on FEI is remarkable at higher thresholds of economic freedom. We conclude that for innovation to promote FEI in Africa, investments in promoting economic freedom are critical.
Keywords: O31; O55; E24; J16; J21; 330; Africa; Innnovation; Economic freedom; Female economic inclusion; GMM